Fitur Produk dan Persepsi Harga: Faktor Penentu Keputusan Pembelian Ponsel Pintar Kalangan Gen Z - Yogatama, Ahmad Nizar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The rapid advancement of smartphone technology has shaped consumer buying behavior, especially among students who depend on these devices for learning and social interaction. This research examines how product features and price perceptions influence students’ decisions to purchase Oppo smartphones in Malang City. Using a quantitative research design, data were obtained through questionnaires distributed to 428 respondents and processed using multiple linear regression analysis. The findings indicate that both product features and perceived price positively and significantly affect purchasing decisions, with product features demonstrating a more dominant role. The proposed model accounts for 66.2% of the variance in purchase decisions, suggesting that these two factors play a substantial part in shaping consumer choices. The results highlight the need for manufacturers like Oppo to focus on continuous feature improvements and maintain competitive pricing to strengthen market appeal. It is also suggested that future studies integrate additional variables such as brand image, marketing promotions, or user experience to offer a broader and more in-depth explanation of the determinants influencing smartphone purchase behavior.